Ecological Scarcity Based Impact Assessment for a Decentralised Renewable Energy System - Hendrik Lambrecht; Steffen Lewerenz; Heidi Hottenroth; Ingela Tietze; Tobias Viere (Energies, 2020)
Increasing the share of renewable energies in electricity and heat generation is the cornerstone of a climate-friendly energy transition. However, as renewable technologies rely on diverse natural resources, the design of decarbonized energy systems inevitably leads to environmental trade-offs. This paper presents the case study of a comprehensive impact assessment for different future development scenarios of a decentralized renewable energy system in Germany. It applies an adapted ecological scarcity method (ESM) that improves decision-support by ranking the investigated scenarios and revealing their main environmental shortcomings: increased mineral resource use and pollutant emissions due to required technical infrastructure and a substantial increase in land use due to biomass combustion. Concerning the case study, the paper suggests extending the set of considered options, e.g., towards including imported wind energy. More generally, the findings underline the need for a comprehensive environmental assessment of renewable energy systems that integrate electricity supply with heating, cooling, and mobility. On a methodical level, the ESM turns out to be a transparent and well adaptable method to analyze environmental trade-offs from renewable energy supply. It currently suffers from missing quantitative targets that are democratically sufficiently legitimized. At the same time, it can provide a sound basis for an informed discussion on such targets.